2016
DOI: 10.1159/000447265
|View full text |Cite
|
Sign up to set email alerts
|

T2 Fluid-Attenuated Inversion Recovery Imaging of Uveal Melanomas and Other Ocular Pathology

Abstract: Background/Aims: This study describes patterns of intraocular lesions on T2 fluid-attenuated inversion recovery (FLAIR) imaging, exploring a prospective role of FLAIR imaging sequence in diagnosis and treatment. Methods: A retrospective study of orbital magnetic resonance imaging (MRI) studies from the years 2000 to 2015 was performed. MRI sequences included: pre-contrast T1-weighted, T2-weighted, T2 FLAIR, and postcontrast T1 and T2 imaging gadolinium, which were evaluated by a neuroradiologist. Two cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It shows progressive significant enhancement after contrast enhancement. PET metabolism suggests that choroidal hemangioma usually has no change in glucose uptake[ 20 , 21 ]. Therefore, enhanced dynamic delayed scanning is of great significance in the diagnosis and differentiation of choroidal hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…It shows progressive significant enhancement after contrast enhancement. PET metabolism suggests that choroidal hemangioma usually has no change in glucose uptake[ 20 , 21 ]. Therefore, enhanced dynamic delayed scanning is of great significance in the diagnosis and differentiation of choroidal hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the use of DW-MRI in the response evaluation of patients with choroidal melanoma undergoing brachytherapy. Other authors have demonstrated the use of other MRI sequences to characterize melanomas, such as the T2 FLAIR sequence and post-contrast sequences to assess vascularization and perfusion of the lesion (37,38). In our work, we used a more objective protocol and intravenous MRI contrast was not administered for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to retinal detachment, necrosis and inflammation are better depicted on T2weighted imaging, as is illustrated in Figure 3 [22,56]. Using the aforementioned features, The signal intensity characteristics of UM on these types of MR-images have been described extensively [10,11,26,28,34,36,37,45,56,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. As almost all intraocular lesions, including UM, are hyperintense on T1-and hypointense on T2-weighted imaging compared to the vitreous, Ferreira [28] proposed to use the choroid and nearby extraocular muscle as reference on T1-and on T2-weighted imaging, respectively.…”
Section: Anatomical Evaluationmentioning
confidence: 99%